Foraging behavior of the Restinga Tyrannulet (Phylloscartes Kronei) (Aves, Tyrannidae) - Gussoni, Carlos Otavio Araujo [UNESP]; Santos, Marcos Cesar de Oliveira [UNESP] (Neotropical Ornithological Soc, Usgs Patuxent Wildlife Research Ctr, 2011)
This study was conducted at Ilha Comprida (24 degrees 20'-25 degrees 03'S; 47 degrees 25'-47 degrees 55'W), São Paulo state, Brazil, in areas of restinga forest between August 2008 and July 2009. A total of 613 foraging maneuvers were observed, keeping a minimum of five minutes between each observation, with the aim of characterizing the foraging behavior of Phylloscartes kronei. This species captures prey mainly with sally-strikes on green leaves between 0,5 and 15 m above the ground. on 40 occasions, it was possible to identify the captured prey, which included Lepidoptera, Orthoptera, and two species of fruits (Clusia criuva and Ternstroemia brasiliensis). Accepted 30 August 2011.
Keywords: Restinga Tyrannulet; Phylloscartes kronei; feeding habits; foraging tactics; Tyrannidae